2010
DOI: 10.1016/j.juro.2010.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Fuhrman Grade Provides Higher Prognostic Accuracy Than Nucleolar Grade for Papillary Renal Cell Carcinoma

Abstract: Each grading system performs well but the predictive accuracy of Fuhrman grade is statistically superior to that of nucleolar grade and only Fuhrman grade provides independent prognostic information on patients with papillary renal cell carcinoma. Thus, Fuhrman grade should be the standard grading system for papillary renal cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 28 publications
3
16
0
Order By: Relevance
“…Many studies have confirmed that Fuhrman grade is correlated with RCC prognosis (20). Recent research found that the Fuhrman grade also provides independent prognostic information for papillary RCC patients (21). We found that TPM1 expression was associated synchronously with both the Fuhrman grade and prognosis in the participating RCC patients.…”
Section: Discussionsupporting
confidence: 48%
“…Many studies have confirmed that Fuhrman grade is correlated with RCC prognosis (20). Recent research found that the Fuhrman grade also provides independent prognostic information for papillary RCC patients (21). We found that TPM1 expression was associated synchronously with both the Fuhrman grade and prognosis in the participating RCC patients.…”
Section: Discussionsupporting
confidence: 48%
“…The prognostic value of Fuhrman grading in PRCC has been reported, but results have been inconsistent, with only a few studies revealing statistical prognostic significance, particularly on multivariate analysis [6,12,19,21,[32][33][34]. Many pathologists rely solely on nucleolar prominence when grading RCC, rather than applying the full Fuhrman grading criteria [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the 3 components of the Fuhrman system were assessed independently for prognostic significance, and only nucleolar prominence was retained on multivariate analysis in PRCCs, proposing the use of nucleolar grading instead of Fuhrman grading for PRCC [11]. However, an additional study revealed the Fuhrman grade to be statistically superior to nucleolar grade [12].…”
Section: Introductionmentioning
confidence: 99%
“…In the largest study of a series of P-RCCs to date, Sukov et al (n=395; including 252 type 1 and 143 type 2 tumors) demonstrated that while both Fuhrman nuclear grade and P-RCC subtype were predictive of death from RCC on univariate analysis (Fuhrman nuclear grade HR 4.0, p<0.001; P-RCC subtype HR 2.2, p=0.01), only Fuhrman nuclear grade retained statistical significance on multivariate analysis including tumor stage (Fuhrman nuclear grade HR 2.8, p=0.001; P-RCC subtype HR 0.86, p=0.66)[11]. Klatt et al and Siki-Paotonu et al similarly showed grade to be more predictive of outcome than subtype on multivariate analysis in large series[9,10]. …”
Section: Discussionmentioning
confidence: 99%
“…In an outcome study of P-RCCs, Allory et al found that subtyping was problematic in 35% of cases; 9% of cases were thus not classified as type 1 or type 2, but were instead designated as an oncocytoid type[6]. Furthermore, most studies recognize that type 1 P-RCCs may demonstrate high nuclear grade, despite being classically associated with low grade and relatively indolent behavior[1,4–6,911]. …”
Section: Introductionmentioning
confidence: 99%